Spirallike and robertson functions of complex order with bounded boundary rotations - Çetinkaya, Asena; Kahramaner, Yasemin; Ahuja, Om P. (My University, 2019)
Using the concept of bounded boundary rotation, we investigate various properties of two new generalized classes of spirallike and Robertson functions of complex order with bounded boundary rotations.
Keywords: Bounded Boundary Rotation; Lambda-Spirallike Function; Lambda-Robertson Function; Integral Operator